Does the watch can detect cardiac arrhythmias? - Kozieł, Paweł; Grodkiewicz, Maria; Artykiewicz , Klaudia; Gorczyca, Kamila; Czarkowski, Marcin; Słupczyńska, Aleksandra; Urbaś, Weronika; Podgórska, Klaudia; Puła, Aleksandra; Krzysiek, Urszula (Journal of Education, Health and Sport, 2023)
Introduction and purpose: The prevalence of cardiac arrhythmias in the population is not exactly known. Since cardiac arrhythmias are often episodic, they cannot be detected by conventional methods such as electrocardiography (ECG), which takes only a few seconds to record. The purpose of this review is to analyze the latest information regarding the use of smart watches to detect cardiac arrhythmias. Material and methods: This review is based on available data collected in the PubMed database published between 2015 and 2022. The search was performed by browsing keywords such as: "smartwatch", "cardiac arrhythmia", "mHealth", "screening", "wearable devices". Results: The results suggest that the detection of atrial fibrillation (AF) using commercially available smartwatches shows very high diagnostic accuracy. Accuracy in smartwatch arrhythmia detection demonstrated a cumulative sensitivity of 100% (95% CI 1.00-1.00) in 16 studies with 5,050 participants. Sensitivity ranged from 25% (95% CI 0.14-0.36) to 100% (95% CI 1.00-1.00), specificity ranged from 68% (95% CI 0.65 -0.70) to 100% (95% Cl 1.00-1.00). Insufficient quality of the PPG signal resulted in the exclusion of some data in many studies. The analyzes showed no difference in diagnostic accuracy between photoplethysmography (PPG) and single-lead electrocardiography used in these devices. Conclusions: The prevalence of arrhythmias in the form of atrial fibrillation and other forms of arrhythmia in the middle-aged and older population is significant. This review highlights the increasing role of electronic devices in the detection of cardiac arrhythmias. Smartwatches show promising accuracy in detecting arrhythmias, but more research is needed to make this method of arrhythmia recognition a common screening method.